Prolegomena: Social Potential of the organization versus employee engagement and job satisfaction - Winkler, Renata A.; Moczulska, Marta (Prolegomena: potencjał społeczny organizacji a zaangażowanie i satysfakcja z pracy, 2019)
The article focuses on the Social Potential of the organization. In accordance with the adopted objective, the components of the potential were described and the conditions of its shaping in the organization were characterized. Taking into account the possible states of combinations of the discussed potential factors, the types of situations important for the assessment of possibilities activating potential were proposed. They were analysed, on the one hand, indicating activities in the field of organization policy, appropriate for shaping, using and developing the potential, and on the other – showing the complexity of the issue and difficulties in the selection of the type of activities. The article shows the role of engagement and satisfaction in this area. It analyses the potential in relation to an individual, a group and an organization
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 3, s. 36-43
Keywords: social potential; organization; job satisfaction; engagement; potencjał społeczny; organizacja; satysfakcja z pracy; zaangażowanie